ANALISIS KUALITAS PRODUK MENGGUNAKAN METODE FAILURE MODE EFFECT ANALYSIS (FMEA) UNTUK MENGIDENTIFIKASI FAKTOR PENYEBAB DOMINAN - Tejaningrum, Ayi; Indri Rustyani, Indri Rustyani (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
Determining the cause of the dominant suitability in a process is the final goal of this study, so the company is able to take action for improvement. The study was conducted at PT. Berdikari Metal Engineering with object research products of Dies Holder Comp Element. The main problem at this time regarding the number of defects is still high, reaching 7.9%. In January to June 2018, the total production reached 735,395 pcs with the number of incompatible products of 52,382 pcs. Case study research methods with quantitative descriptive analysis as the basis for analysis, and Failure Mode Effect Analysis (FMEA) are used as tools in problem solving. Based on field analysis, the highest RPN value is found in the casting process with a value of 400, so companies must improve accuracy in the stages of material refinement, material classification and rolling process so that it reaches a thickness of 0.4 mm and a length of 39.5 mm. Some actions that should be taken by the company include improving HR skills, especially in the process of working accuracy, making changes in factory air temperature, doing engine maintenance. With this proposal, it is expected to reduce product incompatibility by 31%.